Modelling, simulation and dynamic analysis of the time delay model of the recuperative heat exchanger - Debeljković Dragutin Lj. (Tehnika, 2016)
The heat exchangers are frequently used as constructive elements in various plants and their dynamics is very important. Their operation is usually controlled by manipulating inlet fluid temperatures or mass flow rates. On the basis of the accepted and critically clarified assumptions, a linearized mathematical model of the cross-flow heat exchanger has been derived, taking into account the wall dynamics. The model is based on the fundamental law of energy conservation, covers all heat accumulation storages in the process, and leads to the set of partial differential equations (PDE), which solution is not possible in closed form. In order to overcome this problem the approach based on physical discretization was applied with associated time delay on the positions where it was necessary and unavoidable. This is quite new approach, which represent the further extension of previous results which did not include significant time delay existing in the working media. Simulation results, were derived, showing progress in building such a model suitable for further treatment from the position of analysis as well as the needs for control synthesis problem.